Isolation, Characterization and Anti-Multiple Drug Resistant (MDR) Bacterial Activity of Endophytic Fungi Isolated from the Mangrove Plant, Aegiceras corniculatum - Bin, Gong; Yanping, Chen; Hong, Zhang; Zheng, Xiong; Yanqui, Zhang; Huaiyi, Fang; Qiupin, Zhong; Chenxiao, Zhang (Tropical journal of pharmaceutical research, 2014)
Purpose: To isolate, characterize and assess the anti-multiple-drug resistant (MDR) bacterial potential of culturable endophytes from A. corniculatum in Beibu Gulf, China. Methods: The plant parts were collected from healthy-looking A. corniculatum. The endophytes were isolated and identified by colonial morphology and macroscopic characteristics and DNA sequencing of fungal ITS region, and then grouped by phylogenetic analysis. Antibacterial activity was assayed using five human pathogenic bacteria ( B. cereus , P. aeruginosa , E. coli , K. pneumoniae and A. baumanii ) out of which two of them were MDR bacteria. Ethyl acetate extracts from endophytes were prepared, and the minimum inhibitory concentration (MIC) of 3 endophytes was tested using serial 2-fold dilutions of the extract. Results: 61 endophytes obtained from A. corniculatum were grouped into 6 genera (Colletotrichum, Alternaria, Phomopsis, Pestalotiopsis, Guignardia, Cladosporium). Colletotrichum and Pestalotiopsis were the most frequent genera, accounting for colonization frequencies (CF) of 29.5 and 37.7%. Among the rare morphotypes, Alternaria, Phomopsis, Guignardia and Cladosporium were the infrequent genera, accounting for CF ranging from 3.2 to 13.1%. Overall, 3 endophytes, including Glomerella, Guignardia, and Cladosporium, all isolated from the leaves, showed inhibitory activity against five test bacteria in vitro. The endophyte, Colletotrichum, inhibited two MDR K. pneumoniae and A. baumanii, while Guignardia inhibits MDR K. pneumoniae. The MIC of the extract of Colletotrichum against MDR K. pneumoniae was 4 μg/ml, against MDR A. baumanii was 0.5 μg/ml, while MIC of Guignardia to K. pneumoniae was 8 μg/ml. Conclusion: The study demonstrates that endophytes from mangrove plant A. corniculatum were a fascinating fungal reservoir against MDR pathogenic bacteria.